The Impact Of Korean Culture And Its Language Addicted For Indonesian Teenagers Of Korean-Lovers - Siti Rahmi (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2020)
This research focused on (a) the impact of Indonesian teenagers addicted of Korean lovers in learning Korean culture and its language; (b) to find out the advantages and disadvantages of Indonesian teenagers addicted of Korean lovers in learning Korean culture and its language. This research used 50 students of MAN 2 Mataram as the members of the K-lovers as the research participants.This research is qualitative and the data collected through reading some research papers and depth interview with Korean lovers members/community.The data were analyzed by descriptive analysis technique.This results showed that (a) Korean culture and its language was giving many positive and negative impacts for the teenagers of Indonesia addicted of Korean lovers; (b) the researcher found many advantages and disadvantages of Indonesian teenagers of Korean lovers in learning Korean culcure and its language. The results of this study are recommended to (a) all Korean lovers in Indonesia which encourage the development and utilization of learning Korean culture and its language, (b) Korean teachers to use this research as an alternative material and developing students motivation based on their needs, (c) others researcher to carry out further investigation with broader scope of content, focus and locus, and more participants to be involved.